In vitro and in vivo Antioxidant, Antihemolytic and Anti-inflammatory Activities of Santolina chamaecyparissus Extracts. - meriem, Djarmouni; Abderrahmane, Baghiani; Moufida, Adjadj; Lekhmici, Arrar (Pharmacognosy Communications)
Introduction: Santolina chamaecyparissus L. is a small medicinal herb, cultivated in Europe, Asia and Africa due to the antihelmintic, antiseptic, anti spasmodic, bactericidal, fungicidal, digestive and vulnerary properties. Despite this, S. chamaecyparissus aerial part extractions have not been examined for antioxidant, antihemolytic and anti-inflammatory properties. Methods: S. chamaecyparissus aerial parts were extracted with solvents of varying polarity: methanol (crude) extract (CrE) chloroform extract (CHE), ethyl acetate extract (EAE), and aqueous extract (AE). The content of total phenolics, and flavonoids in all the extracts were determined with spectro- photometric methods. Both enzymatic and non-enzymatic methods were used to evaluate the antioxidant activity of the extracts. Antioxidant activity of all the extracts were investigated using free radical scavenging activity (1,1-diphenyl-2-picrylhydrazyl, DPPH• and 2,2’-azino-bis-3-ethyl benzthiazo- line-6-sulfonic acid (ABTS) assay), capacity of the inhibition of linoleic acid peroxidation (β-carotene assay), chelation of metals (iron chelating assay) and inhibition of xanthine oxidase (XO) activity. To investigate antihemolytic activity of the extracts, the 2, 2,-azobis (2-amidinopropane) dihydrochloride (AAPH) assay was used to induce erythrocyte oxidative hemolysis. An in vivo approach was carried out on mice treated with the methanol extract at a dose of 100 mg/kg/day for 21 consecutive days, and one group was treated with vitamin C (vitamin C 50 mg/kg) as a standard drug. To determine the improvement of antioxidant potential, basic biochemical parameters were used in tissue (liver), plasma and whole blood. Phorbol 12-myristate 13-acetate (PMA)-induced ear edema was used to investigate the anti- inflammatory activity of methanolic extract in mice. Results: Among all the extracts analyzed, the EAE exhibited a higher phenolic and flavonoids content (373.83 ± 0.23 mg gallic acid/g, and 61.51±7.86 mg quercetin/g respectively), followed by CE and CHE. DPPH and ABTS scavenging assays showed that EAE exhibited the highest effect in the both assays, with an IC50 of 0.01 mg/ml and 0.0085 mg/ml respectively. All extracts moderately inhibited linoleic acid oxidation, with 57 % inhibition. The CE had a consid- erable chelating activity on ferrous iron (IC50= 0.32 mg/ml). In the enzymatic method by xanthine oxidase, results demonstrated that EAE had the highest XO inhibitory effect on both XO activity and Cyt-c reduction with IC50= 0.052±0.0003 mg/ml and 0.057±0.0006 mg/ml, respectively followed by CHE and CE. In the cellular system, CrE and CHE showed a hemolysis effect with % hemolysis (62.81% ± 1.43), (62.71% ± 1.01). However, EAE provided protection against AAPH-induced hemolysis with 53.67% ± 0.97. The in vivo assay exhibited a significant decrease (79.56%) of the content of malondialdehyde (MDA) in the liver and increased glutathione (GSH) and catalase (71.95% and 59.16% respectively). The methanol extract clearly demonstrated anti-inflammatory effects by reduced ear edema induced by PMA with 61.51%. Conclusion: Our results indicate that the S. chamaecy- parissus extracts (SCE) possesses potent antioxidant and anti-inflammatory properties and may be a valuable natural source that could be applicable to both the medical and food industries.
Keywords: Xanthine oxidase; Total phenolic; Flavonoid compound; Erythrocyte oxidative; Ear edema.